2021
DOI: 10.1039/d1na00021g
|View full text |Cite
|
Sign up to set email alerts
|

LED-driven controlled deposition of Ni onto TiO2 for visible-light expanded conversion of carbon dioxide into C1–C2 alkanes

Abstract: Photocatalytic gas-phase hydrogenation of CO2 into alkanes was achieved over TiO2-supported Ni nanoparticles under LED irradiation at 365 nm, 460 nm and white light. Photocatalysts were prepared using the photo-assisted...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…Sanz-Marco et al [71], synthesized Ni/TiO 2 by photo-assisted deposition of Ni salts under LED irradiation at 365 nm onto TiO 2 P25 nanoparticles in CH 3 OH as a hole scavenger. In this way, the surface of TiO 2 is coated with a 2 nm thick layer and approximately 2 mass% of Ni particles.…”
Section: Mechanism Of the Photocatalytic Co 2 Reductionmentioning
confidence: 99%
“…Sanz-Marco et al [71], synthesized Ni/TiO 2 by photo-assisted deposition of Ni salts under LED irradiation at 365 nm onto TiO 2 P25 nanoparticles in CH 3 OH as a hole scavenger. In this way, the surface of TiO 2 is coated with a 2 nm thick layer and approximately 2 mass% of Ni particles.…”
Section: Mechanism Of the Photocatalytic Co 2 Reductionmentioning
confidence: 99%
“…It has already been demonstrated that the metal-reduced TiO 2 94 with high electron concentration and excellent electron mobility could be used for efficient photocatalytic reduction of CO 2 . Sanz-Marco et al 95 investigated the generation of structural defects in the TiO 2 framework by correlative characterization, and further elucidated the coexistence of strong metal–support interaction between divalent Ni and TiO 2− x . The non- in situ thermal pre-activation of Ni–TiO 2− x strongly promoted the photo-driven/photo-assisted/LED-driven conversion of CO 2 hydrogenation to CO, CH 4 and C 2 H 6 .…”
Section: Application Of Tio2−x-based Photocatalysts For Co2 Reductionmentioning
confidence: 99%
“…It has already been demonstrated that the metal-reduced TiO 2 94 with high electron concentration and excellent electron mobility could be used for efficient photocatalytic reduction of CO 2 . Sanz-Marco et al 95 investigated the generation of structural defects in the TiO 2 framework by correlative characteriz- (Fig. 11).…”
Section: Metal-tio 2−xmentioning
confidence: 99%